Pengaruh Self-Efficacy, Quality of Work Life dan Kompensasi terhadap Retensi Karyawan PT. Antaran Sukses Express di Kota Tangerang - Novi Aisyah; Dewi Puspaningtyas Faeni (Penerbit Goodwood, 2021)
Purpose: This research aimed to examine the effect of Self-Efficacy, Quality of Work Life and Compensation on Employee Retention. This study aimed to see how large the correlation of the three exogenous variable factors on Employee Retention at PT Antaran Sukses Express Tangerang. Research Methodology: The sampling in this research uses a simple random sampling technique, with the number of respondents as many as 100 employees. The technique of methodology used is with the distribution of questionnaires and the statistical testing tool used is SMARTPLS 3.0. Results: The results of this study show that Self-Efficacy (0,207), Quality of Work Life (0,398) and Compensation (0,382) were positively and significantly influential on Employee Retention. Based on the R Square test, it has been indicated that the level of Self-Efficacy, Quality of Work Life and Compensation affect the Retention of Employees to 79.3%, while the remaining 20.7% is affected by other variables outside this study.